FLEKSIBILITAS ISLAM NUSANTARA SEBAGAI MEDIA PENYELESAIAN KONFLIK (Kajian Penerapan Hukum pada Perkawinan Adat Jawa di Desa Pasirmuncang-Banyumas) - Elsa Dwi Jayanti Purwono (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2017)
The purpose of this paper, to examine deeply about the relationship of Islamic law and customary law in the tradition marriage that backed by the different interpretation in the phenomenon of tradition marriage in Indonesia. The distinction sets out from an opinion that the relationship between Islamic law and tradition marriage as a conflicting and dominate each other. Such patterns of interaction ultimately lead to an attitude of mutual blame against the traditions prevailing in society. Before Islam, Hinduism is a religion that dominates almost in all aspects of community life. Nevertheless, Islam does not abolish the tradition that has long lived in society as a whole. Herein comes the interaction between Islam and tradition. The main issues of this research using the method of data collection is done by observation, interview and documentation. Analytical techniques used are qualitative analysis consisting of data reduction, presentation and conclusion. The results of this study indicate that first, the philosophical foundation in tradition marriage is religion. As strong as any society holds strongly to tradition but still can not abandon religion as the basis of human instinct. Second, the relationship between Islamic law and tradition marriage is a harmonious relationship. Tradition marriage as a result of the process of assimilating the law that occurred in the community.